Molecular imprinting technology and poly (ionic liquid)s: Promising tools with industrial application for the removal of acrylamide and furanic compounds from coffee and other foods (2022)
ABSTRACT: Coffee is one of the most consumed beverages in the world. Coffee provides to the consumer special sensorial characteristics, can help to prevent diseases, improves physical performance and increases focus. In contrast, coffee consumption supplies a significant source of substances with carcinogenic and genotoxic potential such as furan, hydroxymethylfurfural (HMF), furfural (F), and acrylamide (AA). The present review addresses the issues around the presence of such toxic substances formed in Maillard reaction (MR) during thermal treatments in food processing, from chemical and, toxicological perspectives, occurrences in coffee and other foods processed by heating. In addition, current strategies advantages and disadvantages are presented along with application of molecular imprinting technology (MIT) and poly (ionic liquid) s (PIL) as an alternative to reduce the furan, HMF, F and AA content in coffee and other foods.